1980
DOI: 10.1126/science.207.4436.1211
|View full text |Cite
|
Sign up to set email alerts
|

The Oaxaca, Mexico, Earthquake of 29 November 1978: A Preliminary Report on Aftershocks

Abstract: Aftershocks of the 29 November 1978 Oaxaca, Mexico, earthquake (surface-wave magnitude Ms = 7.8) define a rupture area of about 6000 square kilometers along the boundary of the Cocos sea-plate subduction. This area had not ruptured in a large (Ms >/= 7), shallow earthquake since the years 1928 and 1931 and had been designated a seismic "gap." The region has also been seismically quiet for small to moderate (M >/= 4), shallow (depth Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…The Oaxaca profile passes through the rupture area of the 1978 M W 7.6 earthquake (Figure 7d). The 1‐month aftershocks for this earthquake extend from 20 to 100 km from the trench [ Singh et al , 1980; Stewart et al , 1981]. As the aftershocks were located relative to the main shock, the relative positions of each earthquake are very well constrained.…”
Section: Mexico Seismogenic Zonementioning
confidence: 99%
“…The Oaxaca profile passes through the rupture area of the 1978 M W 7.6 earthquake (Figure 7d). The 1‐month aftershocks for this earthquake extend from 20 to 100 km from the trench [ Singh et al , 1980; Stewart et al , 1981]. As the aftershocks were located relative to the main shock, the relative positions of each earthquake are very well constrained.…”
Section: Mexico Seismogenic Zonementioning
confidence: 99%
“…The main shock was located at 15.77°N, 96.80°W McNally and Minster, 1981] at a depth of 18 km [Stewart et al, 1981]. Local seismic observations with portable field seismographs showed that the aftershocks were distributed over an area of $80 km (in the E-W direction) Â 65 km (in the N-S direction) and that their hypocenters had increasing depths inland from the trench [Singh et al, 1980], as shown in Figure 2. The fault plane solution has been obtained from P wave first motions at the World-Wide Standardized Seismograph Network (WWSSN) and Mexican stations, yielding two nodal planes (d = 14°, f = 270°and d = 79°, f = 127° [Stewart et al, 1981]), and the northward dipping nodal plane at $14°has been taken as the fault plane to be consistent with the depth distribution of aftershocks.…”
Section: Rupture Processes Of the 1978 And 1999 Oaxaca Earthquakesmentioning
confidence: 99%
“…In the Oaxaca region many studies such as microearthquake observation campaigns, aftershocks studies (for the 1978, 1980, 1982, and 1995 earthquakes), and refraction seismic studies among others have been carried out (e.o~, Ponce et al, 1979;Ntifiez-Cornfi et al, 1979;Singh et al, 1980;Chael and Stewart, 1982;Jimdnez et al, 1983;Astiz and Kanamori, 1984;Yamamoto et al, 1984;Nava, 1984;Ndfiez-Cornfi and Ponce, 1984;Quintanar, 1985;Nava et aL, 1987;Ntifiez-Corntl, 1987;Ntifiez-Corntl and Ponce, 1989;Nfifiez-Cornfi et al, 1993). Thus, the Oaxaca Region is probably the best-studied zone in Mexico from the seismic point of view.…”
Section: Introductionmentioning
confidence: 99%